Spiral Tomography for Determining Implant Angulation:An In Vitro Study - Z. Dalili Kajan; H. Neshandar; G. Adham Fumani; P. Sadr Eshkevari (Tehran University of Medical Sciences, 2008)
Objective: To study the accuracy of spiral tomography in the determination of implant angulation. Materials and Methods: Eighteen gutta-percha filled points on dry mandibles were selected for implant placement. A translucent acrylic template was fabricated for each mandible. After preparing tomographic images (2 mm slice thickness, Cranex Tome), the ideal axis of the implant was traced. The angle between the ideal axis and the tangent line on the alveolar crest in the buccal side was measured and transferred to aluminum sleeves by a protractor. After implant placement, tomographic images were taken again and angles of the actual implants were estimated. In addition, the distances from the tip of the actual and the supposed implants to the buccal cortex were measured. The data were analyzed by paired sample t test with 95% confidence. Results: Less than two-degree difference between angles of the supposed and the actual implants was found in 44.4% of the cases, whilst 33.3% revealed more than five-degree difference. There was a significant statistical difference between the angle of the actual and the supposed implants. There was also a significant statistical difference between the linear distances from the tip of the actual and the supposed implants to buccal cortex (P=0.015) Conclusion: Spiral tomography in combination with template may provide acceptable results concerning implant angulation and prediction of cortical perforation risk.